Hubungan Kebermaknaan Hidup dan Keteraturan Melaksanakan Shalat dengan Psycholohycal Well-Being pada Mahasiswa - Yulianti, Iin; Cahyani, Regita (Universitas Islam Negeri Raden Intan Lampung, 2019)
PPsychologycal well-being affects mental health, social functioning, interpersonal relationships, health, and adaptability. There are several factors that influence psychologycal well-being, such as meaning, purpose in life, and religiosity. The purpose of this study was to determine the relationship between the meaningfulness of life and the regularity of praying with psychologycal well-being in the 2016 class year students at the Faculty of Usuluddin and Religious Studies of UIN Raden Intan Lampung. The hypothesis proposed in this study is that there is a relationship between the meaningfulness of life and the regularity of praying with psychologycal well-being in students. The subjects in this study were students in 2016 at the Faculty of Islamic Studies and Religious Studies of UIN Raden Intan Lampung totaling 70 people taken by propotionate random sampling technique. Data collection methods in this study used three psychological scales namely the psychological well-being scale with 33 items (α = 0.889), the scale of meaningfulness of life with 25 items (α = 0.843) and the regular scale for praying with 49 items (α = 0.958). The data that has been collected is then analyzed using multiple regression analysis techniques assisted by the SPSS 21.0 for Windows program. The results showed that Rx1.2y = 0.530 with a value of F = 13.082 with p = 0.000 (p <0.01) which means the hypothesis is accepted that there is a significant positive relationship between the meaningfulness of life and the regularity of prayer with psychologycal well-being in students with R2 = 0.281. The ability of life and regular prayers contributed 28.1% to psychologycal well-being. The second result with rx1y = 0.302 with p = 0.011 (p <0.05) which showed a significant positive relationship between meaningfulness of life with psychologycal well-being in the 2016 class year students at the Faculty of Usuluddin and Religious Studies of UIN Raden Intan Lampung. The third result with rx2y = 0.518 with p = 0,000 (p <0.05) which shows a significant positive relationship between the regularity of prayer and psychologycal well-being in students.